The Influence of Poly(Lactic Acid) Addition to Thermal Properties of the Blended Polypropylene for Food Packaging Materials - Achmad Hanafi Setiawan; Sanjaya Sanjaya; Fauzan Aulia (Jurnal Kimia Terapan Indonesia, 2017)
The commonly used food packaging materials are made from synthetic polymers derived from petroleum. However, the use of synthetic polymers has negative impacts on the environment, because it is difficult to degrade naturally either by the biotic or abiotic process. Although their complete replacement with eco-friendly packaging films is just impossible to achieve economically, at least for a specific application like food packaging the use of bioplastics should be the future. One of the alternatives is to blend synthetic polymer for instance polypropylene (PP)  with a natural polymer like poly-lactic acid (PLA). Because their mixture is an immiscible blend because they have highly different polarity, it is necessary to add a compatibilizer such as polypropylene-grafted maleic anhydride (PP-g-MAH) in order to increase the properties of its blend miscibility. The objective of this research was to study the influence of PLA addition to the thermal properties of their blend product with PP. The combinations of PP with PLA in the ratios of (80:20); (90:10); (95:5) were prepared and then characterized for their thermal property behaviour by means of TG and DSC. The results showed that increasing the amount of PLA will decrease their enthalpy significantly